1999
DOI: 10.1103/physrevb.60.5179
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy of magnetic interactions inKCuF3andK2

Abstract: The ab initio cluster model approach has been used to study the electronic structure and magnetic coupling of KCuF 3 and K 2 CuF 4 in their various ordered polytype crystal forms. Due to a cooperative Jahn-Teller distortion these systems exhibit strong anisotropies. In particular, the magnetic properties strongly differ from those of isomorphic compounds. Hence, KCuF 3 is a quasi-one-dimensional ͑1D͒ nearest neighbor Heisenberg antiferromagnet whereas K 2 CuF 4 is the only ferromagnet among the K 2 M F 4 serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…B3LYP overestimates the J values by a factor of ∼ 2; the Fock‐35 approach performs better because this fraction of exact exchange has been chosen to optimize the value of the magnetic coupling constants in a set of related compounds 62, 116. This general trend in describing the magnetic coupling constants has been previously analyzed in embedded cluster models of these and other closely related TM systems 71, 73, 82, 85.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…B3LYP overestimates the J values by a factor of ∼ 2; the Fock‐35 approach performs better because this fraction of exact exchange has been chosen to optimize the value of the magnetic coupling constants in a set of related compounds 62, 116. This general trend in describing the magnetic coupling constants has been previously analyzed in embedded cluster models of these and other closely related TM systems 71, 73, 82, 85.…”
Section: Resultsmentioning
confidence: 77%
“…In this approach, second‐order perturbation theory leads to J ∼ t 2 / U , in a two‐electron, two‐center problem, which permits one to relate J and the parameters t and U defining the Hubbard Hamiltonian. Previous calculations with the same model (see references in Section 1) and recent work on cluster models at various levels of theory 61, 71, 73, 82, 120 have shown that the UHF approach can, in principle, account for the superexchange mechanism but provide too small antiferromagnetic coupling constants—usually 20–30% of the experimental value 61, 71, 82, whereas LDA and GGA largely overestimate these magnitudes by a factor of 5–10. This different behavior can be rationalized by the changes in J arising from changes in the effective parameters of the Hubbard Hamiltonian (or, more precisely, in the t / U ratio, i.e., the delocalization/repulsion ratio) in a variable extent, which may be dramatically exaggerated, as in LDA or GGA, or underestimated, as in UHF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, their performance for open-shell systems is by far superior to pure DFT functionals. This is the case, for example, of the calculation of the superexchange coupling constants in transition metal compounds [23][24][25]. For open-shell compounds with strongly localized electrons, as is the case here, the "correct" picture appears to correspond to some percentage of exact exchange in a hybrid functional.…”
Section: Introductionmentioning
confidence: 95%